2011
DOI: 10.1038/pr.2011.8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of whole-body cooling on brain metabolism following perinatal hypoxic–ischemic injury

Abstract: ArticlesClinical Investigation nature publishing group INTRODUCTION: Magnetic resonance imaging (MRI) and spectroscopy (MRs) have proven valuable in evaluating neonatal hypoxic-ischemic injury (hII). RESULTS: MRI scores in the basal ganglia of hII/hT + neonates were significantly lower than hII/hT − neonates, indicating less severe injury and were associated with lower discharge encephalopathy severity scores in the hII/hT + group (P = 0.01). Lactate (Lac) was detected in the occipital gray matter (OGM) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Magnetic Resonance Imaging studies suggest that TH mainly reduces cortical grey matter and BGT lesions (7,8,11,12,(16)(17)(18). However, the optimal timing for seeing MRI lesions and for predicting outcome after TH is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic Resonance Imaging studies suggest that TH mainly reduces cortical grey matter and BGT lesions (7,8,11,12,(16)(17)(18). However, the optimal timing for seeing MRI lesions and for predicting outcome after TH is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional MRI has a high sensitivity for detecting hypoxic-ischaemic brain injury, and there is a strong association between MRI findings and neurodevelopmental outcome (5,6). Several studies have shown a decreased lesion load in HIE after TH (7,8,11,12). Conventional MRI and diffusion-weighted imaging findings evolve considerably in the first postinsult days (9,10), and very early imaging may underestimate the final extent of brain damage.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in NAA concentrations evolve more slowly, and preserved NAA levels with hypothermia have been shown by 1 H MRS performed within 2 weeks after birth [31] . Better preserved Lac/NAA or NAA/Cr ratios are associated with a better clinical encephalopathy severity score and an improved brain microstructure [30,31] . Since TH affects cerebral metabolism, it might alter the prognostic accuracy of 1 H MRS for the long-term outcome.…”
Section: Therapeutic Hypothermiamentioning
confidence: 99%
“…Lac levels in asphyxiated infants are reduced during hypothermia [29] , shortly after rewarming [30] , and in the subacute phase [31,32] . This may reflect the neuroprotective effect of hypothermia on mitochondria in the early phase after HI as well as its potential anti-inflammatory effects during the subacute phase (increased Lac levels at this time point are likely to be related to the presence of brain macrophages [microglia] [33,34] ).…”
Section: Therapeutic Hypothermiamentioning
confidence: 99%
“…For MRS metabolites, developmental changes are well described: NAA increases, while mI decreases with increasing GA at scan. But gestational age at birth and post-natal age may also affect the outcome of a scan done at term age [33][34][35][36]. Gestational age at birth may be important if subsequent development of the brain region depends heavily on the stage at which the infant was exposed to the extrauterine environment, or if brain injury occurs near the time of birth [37].…”
Section: Correlational Analysismentioning
confidence: 99%